Intestinal Perforation as a Complication of Induced Abortion - a Case Report and Literature Review - Alam, IP; Pervin, Z; Haque, MA (Faridpur Medical College Journal, 2012)
Intestinal perforation is a rare complication of induced abortion but it is not rare in our country. It is most commonly seen in countries in which abortions are performed by people without proper training and with sharp pointed instruments without knowledge of anatomy. Bowel perforation occurs when the posterior vaginal wall or uterus is violated, allowing the instrument to pierce underlying structures. The ileum and sigmoid colon are the most commonly injured portions of bowel due to their anatomic location. Here we discussed a woman who sustained a perforation at anterior rectal wall from abortion and was managed successfully. DOI: http://dx.doi.org/10.3329/fmcj.v7i1.10299 Faridpur Med. Coll. J. 2012;7(1): 46-49